The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.12732/ijpam.v102i3.10
|View full text |Cite
|
Sign up to set email alerts
|

ON A SEQUENCE OF TRIDIAGONAL MATRICES WHOSE DETERMINANTS ARE FIBONACCI NUMBERS $F_{n+1}$

Abstract: In this paper, we generalize two previous individual results on connection special tridiagonal matrices to Fibonacci numbers, as we found a sequence of tridiagonal matrices which are equal to Fibonacci numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…They showed that det(M α,β (k)) = F αk+β and det(T α,β (k)) = L αk+β , i.e., the determinants form subsequences of Fibonacci and Lucas numbers. For related results we refer to the works [35], [42] and [13].…”
Section: Fibonacci Numbers As Determinants Of Certain Special Matricesmentioning
confidence: 99%
“…They showed that det(M α,β (k)) = F αk+β and det(T α,β (k)) = L αk+β , i.e., the determinants form subsequences of Fibonacci and Lucas numbers. For related results we refer to the works [35], [42] and [13].…”
Section: Fibonacci Numbers As Determinants Of Certain Special Matricesmentioning
confidence: 99%
“…He was 1 st European mathematician which work on Indian and Arabian mathematics. He gave a special type sequence [5,6,9] ‫ܨ‬ = ‫ܨ‬ ିଵ + ‫ܨ‬ ିଶ , ݊ ≥ 2 (1) With initial Term ‫ܨ‬ = 0 and ‫ܨ‬ ଵ = 1 Edouard Lucas dominated the field recursive series during the period 1878-1891 he was 1 st mathematician who applied Fibonacci's name for sequence (1) and it has been known as Fibonacci sequence since then. Lucas sequence given by [10,11,12].…”
Section: Introduction 11 Fibonacci Numbersmentioning
confidence: 99%
“…Many authors derived the similar types of matrices which determinants or permanents are related to Fibonacci numbers or different kinds of their generalizations, e. g. k-generalized Fibonacci numbers, see [5], [7] [2], [6], [9] and [11]. Now we turn our attention to the relation of determinants of special tridiagonal matrices with Fibonacci numbers.…”
Section: Introductionmentioning
confidence: 99%